Arboretum The Gallery of Sukapura: Sebuah Usaha untuk Mewujudkan Pembangunan Berkelanjutan - Ridha Nuralia Fauziah Fauziah; Christian Febriana (Pencerah, 2023)
This study examines The Gallery of Sukapura, a community empowerment program designed to save the environment and ecotourism through protection and conservation efforts using a sustainable development approach. This study was conducted in Sukapura Village in West Java Province. The study's goal is to discover how the empowerment program can be used for education, recreation, and research, as well as how it can help the Sukapura community's economy. The research method used is a narrative approach with interviews, observation, and documentation studies with narration with informants chosen by snowball sampling. The obtained data was then analyzed in three ways: data display, data transcription, and data verification. The study's findings indicate that The Gallery of Sukapura has the potential to become a community empowerment program that provides value and benefits because the concept was developed while protecting the existing ecosystem of flora and fauna, ensuring a balance between saving the earth and human development. According to the findings of this study, empowerment has the potential to become a pioneer of environmental protection, a vehicle for education-recreation, and a means of increasing the community's economy.